(untitled) (Journal of actual problems of jurisprudence, 2018)
The article is devoted to determination of ways of enforcement of the principle of the rule of law in the administration of justice in administrative cases. With this purpose, the content of the principle of the rule of law at the modern stage of development of legal doctrine, as well as its legal basis are analyzed. The the ratio of the enforcement of the principle of the rule of law and analogy of law is researched. Keywords: rule of law, legality, administrative proceedings, justice, the interpretation of norms of the law.